2018
DOI: 10.1051/0004-6361/201731269
|View full text |Cite
|
Sign up to set email alerts
|

Seismic probing of the first dredge-up event through the eccentric red-giant and red-giant spectroscopic binary KIC 9163796

Abstract: Context. Binaries in double-lined spectroscopic systems (SB2) provide a homogeneous set of stars. Differences of parameters, such as age or initial conditions, which otherwise would have strong impact on the stellar evolution, can be neglected. The observed differences are determined by the difference in stellar mass between the two components. The mass ratio can be determined with much higher accuracy than the actual stellar mass. Aims. In this work, we aim to study the eccentric binary system KIC 9163796, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 142 publications
(207 reference statements)
2
47
0
Order By: Relevance
“…Such a two-layer model is commonly used in the representative forward-modelling approach in asteroseismology. Recent theoretical and observational results by Di Mauro et al (2016) and Beck et al (2018), respectively, have confirmed that this simplification can be used.…”
Section: Appendix B: Frequency-averaged Dissipation Of the Dynamical mentioning
confidence: 78%
“…Such a two-layer model is commonly used in the representative forward-modelling approach in asteroseismology. Recent theoretical and observational results by Di Mauro et al (2016) and Beck et al (2018), respectively, have confirmed that this simplification can be used.…”
Section: Appendix B: Frequency-averaged Dissipation Of the Dynamical mentioning
confidence: 78%
“…When the asteroseismic surface rotation rate is roughly equal to the independent measurement of the surface rotation, the star rotates as a solid body in the convection zone. Beck et al (2018) applied the above approach to the primary component of the binary KIC 9163796 and showed that the amount of differential rotation in the convection zone is small, meaning that the convection zone is nearly rotating as a solid body. This could provide important hints for underlying angular momentum transport mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Internal rotation rates as a function of depth have been estimated for a number of red giants using a forward modelling approach (Beck et al 2014(Beck et al , 2018 or by means of rotational inversions (Deheuvels et al 2012(Deheuvels et al , 2014Di Mauro et al 2016Triana et al 2017). However, the exact shape of the internal rotation profile remains unknown, as only core and surface rotation rates can currently be measured.…”
Section: Introductionmentioning
confidence: 99%
“…One obvious example is testing tidal interaction theories [e.g., (Remus et al, 2012)]. Beck et al (Beck et al, 2018a) used a sample of binaries with at least one red-giant star to show that the equilibrium tide is sufficient to explain the distribution of the measured orbital eccentricities and periods. As another important example, a prediction of stellar evolution theory is that stars climbing the red-giant branch will "dredge-up" nuclear-processed material as the surface convection zone deepens, potentially altering the surface composition.…”
Section: Precision Stellar Interior Physicsmentioning
confidence: 99%